A curious case of agreement between conventional thermobarometry and phase equilibria modelling in granulites: New constraints on P–T estimates in the Antarctica segment of the Musgrave–Albany–Fraser–Wilkes Orogen. (12th September 2017) - Morrissey, Laura J.; Hand, Martin; Kelsey, David E.
Abstract: The Windmill Islands region in Wilkes Land, east Antarctica, preserves granulite facies metamorphic mineral assemblages that yield seemingly comparable P–T estimates from conventional thermobarometry and mineral equilibria modelling. This is uncommon in granulite facies terranes, where conventional thermobarometry and phase equilibria modelling generally produce conflicting P–T estimates because peak mineral compositions tend to be modified by retrograde diffusion processes. In situ U–Pb monazite geochronology and calculated metamorphic phase diagrams show that the Windmill Islands experienced two phases of high thermal gradient metamorphism during the Mesoproterozoic. The first phase of metamorphism is recorded by monazite ages in two widely separated samples and occurred at c . 1, 305 Ma. This event was regional in extent, involved crustally derived magmatism and reached conditions of 3.2–5 kbar and 690–770°C corresponding to very high thermal gradients of >150°C/kbar. The elevated thermal regime is interpreted to reflect a period of extension or increased extension in a back‐arc setting that existed prior to c . 1, 330 Ma. The first metamorphic event was overprinted by granulite facies metamorphism at c . 1, 180 Ma that was coeval with the intrusion of charnockite. This event involved peak temperatures of 840–850°C and pressures of 4–5 kbar. A phase of granitic magmatism at c . 1, 250–1, 210 Ma, prior to the intrusion of the charnockite, is interpreted to reflect a phase of compression within an overall back‐arc setting. Existing conventional thermobarometry suggests conditions of 4 kbar and 750°C for M1 and 4–7 kbar and 750–900°C for M2 . The apparent similarities between the phase equilibria modelling and existing conventional thermobarometry may suggest either that the terrane cooled relatively quickly, or that the P–T ranges obtained from conventional thermobarometry are sufficiently imprecise that they cover the range of P–T conditions obtained in this study. However, without phase equilibria modelling, the veracity of existing conventional P–T estimates cannot be evaluated. The calculated phase diagrams from this study allow the direct comparison of P–T conditions in the Windmill Islands with phase equilibria models from other regions in the Musgrave–Albany–Fraser–Wilkes Orogen. This shows that the metamorphic evolution of the Wilkes Land region is very similar to that of the eastern Albany–Fraser Orogen and Musgrave Province in Australia, and further demonstrates the remarkable consistency in the timing of metamorphism and the thermal gradients along the 5, 000 km strike length of this system.